The effects of elevated CO2 and eutrophication on surface elevation gain in a European salt marsh. (9th July 2016) - Reef, Ruth; Spencer, Tom; Mӧller, Iris; Lovelock, Catherine E.; Christie, Elizabeth K.; McIvor, Anna L.; Evans, Ben R.; Tempest, James A.
Abstract: Salt marshes can play a vital role in mitigating the effects of global environmental change by dissipating incident storm wave energy and, through accretion, tracking increasing water depths consequent upon sea level rise. Atmospheric CO2 concentrations and nutrient availability are two key variables that can affect the biological processes that contribute to marsh surface elevation gain. We measured the effects of CO2 concentrations and nutrient availability on surface elevation change in intact mixed‐species blocks of UK salt marsh using six open‐top chambers receiving CO2 ‐enriched (800 ppm) or ambient (400 ppm) air. We found more rapid surface elevation gain in elevated CO2 conditions: an average increase of 3.4 mm over the growing season relative to ambient CO2 . Boosted regression analysis to determine the relative influence of different parameters on elevation change identified that a 10% reduction in microbial activity in elevated CO2 ‐grown blocks had a positive influence on elevation. The biomass of Puccinellia maritima also had a positive influence on elevation, while other salt marsh species (e.g. Suaeda maritima ) had no influence or a negative impact on elevation. Reduced rates of water use by the vegetation in the high CO2 treatment could be contributing to elevation gain, either directly through reduced soil shrinkage or indirectly by decreasing microbial respiration rates due to lower redox levels in the soil. Eutrophication did not influence elevation change in either CO2 treatment despite doubling aboveground biomass. The role of belowground processes (transpiration, root growth and decomposition) in the vertical adjustment of European salt marshes, which are primarily minerogenic in composition, could increase as atmospheric CO2 concentrations rise and should be considered in future wetland models for the region. Elevated CO2 conditions could enhance resilience in vulnerable systems such as those with low mineral sediment supply or where migration upwards within the tidal frame is constrained.